Effects of algae particle size on the breathing and feeding of filter‐feeding silver carp (Hypophthalmichthys molitrix Val.). (25th July 2016) - Zhao, Zhigang; Dong, Shuanglin; Wang, Fang; Tian, Xiangli; Gao, Qinfeng; Xu, Qiyou; Yu, Jianhua
Abstract: A variety of parameters associated with breathing and feeding of silver carp were measured in response to declines in dissolved oxygen (DO) levels when the fish were fed microalgae Padorina morum ( PM group) and Chlorella ellipsoidea ( CE group), respectively, to explore the relationship between breathing and feeding while filtering microalgae particles at different DO levels. The results indicated that (i) respiratory frequency ( f R ) of the fish in CE group were higher significantly than those in PM group at DO levels of 0.98–7.49 mg/L ( P < 0.05); respiratory stroke volume (V S.R ), gill ventilation ( V G ) and V G /VO2 the fish in two groups began to increase sharply while DO levels declined to below 4.04 mg/L ( P < 0.05); oxygen extraction efficiency (EO2 ) of the fish in two groups increased significantly with decline of DO levels from 7.49 mg/L to 0.98 mg/L ( P < 0.05); (ii) the infiltration rate (FR) and filtering efficiency (E) of the fish in two groups began to decrease significantly while DO levels declined to below 4.04 mg/L ( P < 0.05); clearance rate (CR) of fish in PM group was sixfold higher than that in CE group at DO levels of 0.98–7.49 mg/L ( P < 0.05). In addition, antifiltering response appeared at DO levels of 2.21 mg/L and 0.98 mg/L in both groups. This study indicated that 'filtration effect' is dominant when the fish filter algae particles larger than its gill raker gaps, while the 'food sinking effect' is dominant when the fish filter algae particles smaller than its gill raker gaps.